Foreign Trade Security Cooperation Between Ukraine and China (Economic journal of Lesya Ukrainka Volyn National University, 2016)
The article analyzes the background and current export-import trade relations between Ukraine and the countries of the Asia-Pacific region, including with China. The potential of the Asia-Pacific region described. Strengthening the role of China in the global economy due to the global economic center shifting to Asia is proved. Institutional supplement for cooperation between Ukraine and China is studied. The volume and structure of trade between Ukraine and China for the years 2010–2014 are presented and analyzed. The structure of imports from China is balanced, it equally represents all commodity groups, dominatedby products with high added value, while Ukrainian exports are virtually monocultural and raw materials (ore). The priorities of foreign security relations, expand and deepen cooperation with China justified. The priorities of cooperation and strengthen the safety of foreign economic cooperation between Ukraine and China
Keywords: foreign trade security, economic cooperation, Ukraine, China strategic partnership